891 Fasting Times in Trauma List Patients. (12th October 2021) - Gabriels, S; Goru, P; Haque, S; Hayat, M
Abstract: Introduction: To reduce the risk of regurgitation and aspiration of gastric contents, patients are to fast before anaesthesia. However, prolonged periods of fasting have been found to be unnecessary and potentially harmful. Our aim was to compare pre-operative fasting times in trauma patients against the AAGBI (Association of Anaesthetists of Great Britain and Ireland) guidelines and highlight areas for improvement. The AAGBI recommends minimum fasting periods of: six hours for solid food, infant formula, or other milk. four hours for breast milk. two hours for clear non-particulate and non-carbonated fluids. Method: 50 patients were audited in each cycle. Data were collected prospectively using questionnaires in the initial audit and by interviewing patients in the re-audit. Patients in ITU and those with dementia were excluded. Questions included fasting instructions given, time of the last meal and drink (including kind of drink), IV fluids administration. Anaesthetic notes were checked for time of induction of anaesthesia. Results: Average time fasted for food was 17.09 hours and 9.32 hours for water. In the re-audit, average time fasted was 16.43 hours for food and 5.27 hours for water. All the patients received information as to when they could eat or drink until. None of them was told 'midnight'. Conclusions: Although there was an improvement, this was still beyond the guidelines. The results highlighted the importance of regularly reviewing the fasting status throughout the day in order to achieve the standard.